DEHYDROPOLYMERIZATION OF BIS(SILYL)ALKYLBENZENES TO HIGHLY CROSS-LINKED POLYSILANES, CATALYZED BY GROUP-4 METALLOCENE COMPLEX - WOO, HG; KIM, SY; KIM, WG; YEON, SH; CHO, EJ; JUNG, IN (KOREAN CHEMICAL SOC, 1995)
Bis(silyl)alkylbenzenes such as bis(1-sila-sec-butyl)benzene (1) and 2-phenyl-1,3-disilapropane (2) were prepared in high yields by reduction of the corresponding chlorosilanes with LiAlH4. The dehydropolymerization of 1 and 2 was carried out with group 4 metallocene complexes generated in situ from Cp(2)MCl(2)/Red-Al and Cp(2)MCl(2)/n-BuLi (M=Ti, Hf), producing two phases of polymers. The TGA residue yields of the insoluble polymers were in the range of 64-74%. The molecular weights of the soluble polymers produced ranged from 700 to 5000 (M(w) vs polystyrene) and from 500 to 900 (M(n) vs polystyrene). The dehydropolymerization of 1 and 2 seemed to initially produce a low-molecular-weight polymer, which then underwent an extensive cross-linking reaction of backbone Si-H bonds, leading to an insoluble polymer.
Keywords: BOND METATHESIS MECHANISM; DEHYDROGENATIVE POLYMERIZATION; PRIMARY ORGANOSILANES; HIGH POLYMERS; SILANES; ZIRCONOCENE; OLIGOSILANES; TITANOCENE; OLIGOMERS